The Effect Of Chemical Surface Treatment On Mechanical Performance Of Electrically Conductive Adhesives - Sheikh Md Fadzullah, Siti Hajar; Omar, Ghazali; Salim, Mohd Azli; Mansor, Muhd Ridzuan; Wan Abdul Rahman, Wan Ahmad; Nasaruddin, Muhamad Muaz; Mustafa, Zaleha (Novel Carbon Resource Sciences, 2020)
Adhesion strength of electrically conductive adhesive (ECA) could be enhanced through surface treatment. This paper characterizes the multiwalled carbon nanotube (MWCNT) filled ECA with varying MWCNT filler loading. Here, the focus is on the effect of chemical treatment on aluminium substrate surface treatment onto the adhesion strength of the ECA as per ASTMD 1002. The chemically etched aluminum substrate provides the largest effective bond area between ECA/substrate interface, with the highest shear strength of the ECA. More specifically, the ECA with 6 wt.% MWCNT filler loading exhibit an optimum lap shear strength, showing an adhesive-cohesive failure mode.